Crystallization Properties of Polycaprolactone Induced by Different Hydroxyapatite Nano-Particles - Guang-Mei, Chen; Tie-Mei, Zou; Lei, Chen; Yi-Ping, Huang (Asian Journal of Chemistry, 2010)
Polycaprolactone (PCL) composites were synthesized by two grades of hydroxyapatite (HA) nano-particles, namely, HA1 (prepared in our laboratory) and HA2 (purchased from commercial). The molar ratio of Ca/P for HA1 analyzed by ICP was 1.68 and 1.60 for HA2. The number average molecular weight of the polymers was measured by 1H NMR. The crystallization behaviour of the samples was characterized by DSC, XRD and polarized light micrographs (PLM). The results indicated that polycaprolactone prepared by different HA nano-particles had slightly change in the number average molecular weight for the same content of HA. But the crystallization behaviour of the nano-HA/PCL samples had identical change tendency with the change of HA content in the samples. Both grades of HA nano-particles could increase the crystallization temperatures (Tc) of PCL from 25-28 °C, decrease the melting temperatures (Tm) from 61-55 °C and decrease the crystallinity of PCL from 55 to 39 %. When the content of nano-HA in the composites was 5 wt %, the thermal decomposition temperature could be elevated about 100 °C. The results for measurements suggested that the nano-HA/PCL composites with analogical properties could be obtained by the same content of HA either prepared in our laboratory or purchased from commercial.